How have studies of ancient DNA from sediments contributed to the reconstruction of Quaternary floras?. Issue 2 (24th September 2015) - Birks, H. John B.; Birks, Hilary H.
Summary: Ancient DNA (aDNA) from lake sediments, peats, permafrost soils, preserved megafaunal gut contents and coprolites has been used to reconstruct late‐Quaternary floras. aDNA is either used alone for floristic reconstruction or compared with pollen and/or macrofossil results. In comparative studies, aDNA may complement pollen and macrofossil analyses by increasing the number of taxa found. We discuss the relative contributions of each fossil group to taxon richness and the number of unique taxa found, and situations in which aDNA has refined pollen identifications. Pressing problems in aDNA studies are contamination and ignorance about taphonomy (transportation, incorporation, and preservation in sediments). Progress requires that these problems are reduced to allow aDNA to reach its full potential contribution to reconstructions of Quaternary floras. Contents Summary 499 I. Introduction 499 II. Research approaches and investigative stages 500 III. Types of plant aDNA studies 500 IV. aDNA and fossil identifications 500 V. aDNA as the sole basis for floristic reconstructions 500 VI. Comparative aDNA, pollen, and/or macrofossil studies 501 VII. Future challenges 502 VIII. Conclusions and appraisal 504 Acknowledgements 504 References 505